2018
DOI: 10.1016/j.humov.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of running retraining on biomechanical factors associated with lower limb injury

Abstract: Injury risk is an important concern for runners; however, limited evidence exists regarding changes to injury risk following running style retraining. Biomechanical factors, such as absolute peak free moment, knee abduction impulse, peak foot eversion and foot eversion excursion, have been shown to predict lower limb injury. The aim of this study was to assess the effects of Pose running retraining on biomechanical factors associated with lower limb running injury. Twenty uninjured recreational runners were pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…Briefly, this method proposes running with a forward trunk lean, a more flexed position at touch-down, a mid-foot striking style, and a low range of arm motion [119]. A previous study demonstrated that adopting this particular RT did not result in changes in specific biomechanical factors associated with injury risk, nor in running performance [120]. Also, RE deteriorated when RT was altered with this method by reducing stride length and vertical oscillations [121].…”
Section: Running Techniquementioning
confidence: 99%
“…Briefly, this method proposes running with a forward trunk lean, a more flexed position at touch-down, a mid-foot striking style, and a low range of arm motion [119]. A previous study demonstrated that adopting this particular RT did not result in changes in specific biomechanical factors associated with injury risk, nor in running performance [120]. Also, RE deteriorated when RT was altered with this method by reducing stride length and vertical oscillations [121].…”
Section: Running Techniquementioning
confidence: 99%
“…It has been reported that the most effective strategy for reducing high-risk factors for RRI-such as impact loading-is the introduction of real-time feedback related to kinetics and/or kinematics and strike pattern. [26][27][28]35,38 Therefore, the present study included both short-term gait retraining with visual biofeedback and static training with visual biofeedback (after gait retraining with visual biofeedback) based on methodologies used in previous studies. The goal was to reduce the static and dynamic plantar load on the medial and lateral rearfoot.…”
Section: Discussionmentioning
confidence: 99%
“…Dunn et al 28 performed running retraining that resulted in increases in foot strike index, knee flexion at initial contact, and ankle dorsiflexion at terminal stance. In the gait retraining of recreational runners, one possible explanation for the benefit of forefoot and rearfoot plantar loading rate reduction in the static condition may be better control of foot pronation; this has been well verified by changing the postural pattern back to normal, thereby reducing the medial body weight projection with regard to the support point of the calcaneus and metatarsals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations